Polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy: report of two cases - Joanisson Rubens Gomes Diniz; Katie Moraes de Almondes; Clécio Godeiro Júnior; Rodrigo Alencar e Silva (Dementia & Neuropsychologia)
ABSTRACT The polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy–Nasu-Hakola disease–is a hereditary and progressive pathology, which is mainly associated with pre-senile dementia and changes in bone architecture. Objective To report two rare cases of sibling patients treated with early-onset dementia syndrome with genetic etiology, and to review the literature on the topic. Methods Review of medical records, interviews and recording of the diagnostic methods to which patients were subjected. From this, a report was prepared of two cases who began behavioral changes in the third decade of life, who developed, at different times, symptoms of similar cognitive impairment. Bibliographic research carried out in the United States National Library of Medicine (PubMed), Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Health Sciences Literature (LILACS), UpToDate and Scientific Electronic Library Online (SciELO) databases for bibliographic review. Results Two clinical cases with genetic confirmation of Nasu-Hakola disease and a brief literature review were described. Conclusion These cases illustrate a presentation of pre-senile dementia syndrome and reinforce the importance of adequate diagnosis for timely treatment, humanized multidisciplinary follow-up aiming to improve quality of life, as well as genetic and family counseling.